2020
DOI: 10.3390/foods10010002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cavitation Jet Treatment on the Structure and Emulsification Properties of Oxidized Soy Protein Isolate

Abstract: This study examined the ability of cavitation jet processing to regulate the oxidation concentrations with 2,2’-azobis (2-amidinopropane) dihydrochloride (AAPH) (0.2, 1, and 5 mmol/L) and the structure and emulsification of soy protein isolate (SPI). The tested properties included particle size distribution, hydrophobic properties (sulfhydryl group (SH) and disulfide bond (S-S) contents, surface hydrophobicity (H0)), emulsifying properties (particle size and ζ-potential of emulsions, emulsification activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 53 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…The results also showed promotion of α‐helix, β‐turn and random coil as the increase of roasting strength, this might be due to contribution of roasting treatment to the formation of disulfide or isopeptide bonds (Xiang et al, 2020). As report goes, decreased β‐sheet and the increase of α‐helix and random coil indicated that rigid structure of protein molecule was weakened, flexible structure was enhanced, and molecule changed from ordered structure to disordered structure (He et al, 2020). This is one of the reasons for the improved protein functional properties.…”
Section: Resultsmentioning
confidence: 99%
“…The results also showed promotion of α‐helix, β‐turn and random coil as the increase of roasting strength, this might be due to contribution of roasting treatment to the formation of disulfide or isopeptide bonds (Xiang et al, 2020). As report goes, decreased β‐sheet and the increase of α‐helix and random coil indicated that rigid structure of protein molecule was weakened, flexible structure was enhanced, and molecule changed from ordered structure to disordered structure (He et al, 2020). This is one of the reasons for the improved protein functional properties.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 40 ml of GSPI and 10 ml of soybean oil were put into a 100-ml beaker, homogenized at a speed of 12,000 r/min for 2 min using T25 digital homogenizing and dispersing instrument (IKA, Germany) ( 36 ). Then, 50 μl was taken from the bottom and mixed with 5 ml of 0.1% SDS, and the absorbance values were measured at 500 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The national standards GB/T 3216-2016 and GB/T18149-2017 use the 3% drop in the head as the criterion for determining the completion of the cavitation test. During the test, the 3% drop in head occurs during the later stage of cavitation development on the test bench [25][26][27][28][29].…”
Section: B Mixed-flow Pump Hydraulic Model Cavitation Noise Variation...mentioning
confidence: 99%